The value of Chlortetracycline for steers on a wintering, grazing and fattening program - Smith, E.F.; Koch, B.A.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Twenty good to choice Hereford steer calves from near Ft. Davis, Texas, were randomly divided into two lots. One group served as the control: the other was treated in a similar way except that each animal received 70 mgs. of chlortetracycline (aureomycin) daily.
Keywords: Beef; Chlortetracycline; Sorghum grain; Bluestem pasture